The APPS: an outcome score for the acute respiratory distress syndrome - Villar, Jesús; Kacmarek, Robert M. (Journal of Thoracic Disease; Vol 8, No 10 (October 01, 2016): Journal of Thoracic Disease, 2016)
The acute respiratory distress syndrome (ARDS) is an acute and intense inflammatory process of the lungs that develops in response to pulmonary and systemic insults to the alveolar-capillary membrane, resulting in increased vascular permeability and development of interstitial and alveolar edema. Although ARDS is clinically characterized by acute hypoxemic respiratory failure refractory to oxygen therapy, over the years we have used several different diagnostic schemas, all based on a combination of clinical, oxygenation, radiographic, and hemodynamic abnormalities to identify these patients (1,2).